Generalized Power Flow Algorithms for Monopolar DC Networks Using Broyden’s Method - Montoya Giraldo, Oscar Danilo; Ramírez-Vanegas, Carlos Alberto; Mesa, Fernando (Ingeniería, 2025)
Solving the power flow problem in transmission networks is crucial for ensuring the reliable and efficient operation of electrical power systems. Power flow analysis allows engineers to determine the voltage, current, and power flows of a network, which is essential for maintaining system stability and avoiding overloads. Accurate power flow solutions aid in identifying potential issues such as voltage drops, line losses, and system inefficiencies, enabling the proactive maintenance and optimization of the grid. This analysis is vital for integrating renewable energy sources, as it ensures an effective power distribution, even when dealing with variable generation. Ultimately, solving the power flow problem enhances the overall resilience, reliability, and economic performance of the transmission network, supporting a stable supply of electricity to consumers.